Neodymium oxide (ND2O3) as passive q-switcher for pulsed fiber laser generation in c-band region - Ab Rahman, Mohd Fauzi; Zainal Roslan, Ilyana Amalin; Abdul Latiff, Anas (2022)
This work demonstrate Neodymium Oxide (Nd2O3) film as a passive saturable absorber (SA) for pulse generation within C-band region. The saturable absorber was fabricated from Nd2O3 powder, and polyvinyl alcohol (PVA) was used to form a film. The all-fiber ring cavity configuration was used in the experiment. The Q-switching operated with the pump power from 60 mW to 120 mW. The repetition rate increases from 52 kHz to 77 kHz, while the pulse width shown decrement of 7.4 µs to 5.3 µs. The signal-to-noise ratio obtained of the fundamental frequency is 64 dB. The maximum output power and pulse energy are 3.6 mW and 4.6 nJ respectively. The maximum peak power obtained is 0.87 mW.